2017
DOI: 10.1016/j.ekir.2016.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Negative Staining for COL4A5 Correlates With Worse Prognosis and More Severe Ultrastructural Alterations in Males With Alport Syndrome

Abstract: IntroductionAlport syndrome (AS) is a genetic disorder characterized by progressive hematuric nephropathy with or without sensorineural hearing loss and ocular lesions. Previous studies on AS included mostly children.MethodsTo determine the prognostic value of loss of staining for collagen type IV alpha 5 (COL4A5) and its relationship with the ultrastructural glomerular basement membrane alterations, we performed direct immunofluorescence using a mixture of fluorescein isothiocyanate-conjugated and Texas-red c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…Previously, it was reported that male patients with XLAS with positive staining for a5(IV) in kidney tissue tended to show milder clinical phenotypes and carried nontruncating mutations (mostly missense mutations). 7,16 In our cohort, three of seven patients carrying nontruncating transcriptional variants were a5(IV) positive. In contrast, no patients carrying nontruncating transcriptional variants were a5(IV) positive (Supplemental Table 4).…”
Section: Discussionmentioning
confidence: 82%
“…Previously, it was reported that male patients with XLAS with positive staining for a5(IV) in kidney tissue tended to show milder clinical phenotypes and carried nontruncating mutations (mostly missense mutations). 7,16 In our cohort, three of seven patients carrying nontruncating transcriptional variants were a5(IV) positive. In contrast, no patients carrying nontruncating transcriptional variants were a5(IV) positive (Supplemental Table 4).…”
Section: Discussionmentioning
confidence: 82%
“…For P19, in addition to the manifestation of nephrotic range proteinuria, the patient also had hearing loss when he was diagnosed. Similarly, Samar et al [ 23 ] stated that negative staining of α5 chain was correlated with the worse prognosis and more severe ultrastructural alterations in AS men. Additionally, eight patients had intact staining of α 5 chain.…”
Section: Discussionmentioning
confidence: 94%
“…For P19, besides presenting proteinuria of nephrotic range, he had hearing loss when he was diagnosed. Similarly, Samar et al [16] stated that negative staining for α5 chain correlates with worse prognosis and more severe ultrastructural alterations in males with Alport Syndrome. There were still 8 patients who had intact staining for α 5 chain.…”
Section: Discussionmentioning
confidence: 95%